Transição de juízos : a indenização da sentença penal e seu cumprimento no cível - Queiroz, Mariah Oliveira Santos de (2018)
Once stipulated a liquid compensation at the guilty criminal sentence, it goes to the execution phase at the civil court. The current wording of the art. 387, IV, CPP completes a decade of existence this year. This work originates from reflexions on the literature concerning this issue and aims to perform an analysis of the renovations done at the last decades, both at civil procedure and at criminal procedure, about the court transition to this execution, culminating at the CPC/15. It also investigates to what extent these reforms are mismattched concerning the effectiveness at the beginning of the satisfaction of the criminal compensation, especially at this momento f passage, from the criminal to the civil.